(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Three articles are devoted to the study of proverbs in linguistics. The visual characteristics of proverbs, their analytical conclusion, semantic analysis and pragmatics. The role of proverbs in speech, their cognitive significance, is considered. The study is a theory of the organization of proverbs from a linguistic point of view and the development of their practical use.